Probing entanglement dynamics and topological transitions on noisy intermediate-scale quantum computers - Huai-Chun Chang; Hsiu-Chuan Hsu; Yu-Cheng Lin (Physical Review Research)
We simulate quench dynamics of the Su-Schrieffer-Heeger (SSH) chain on IBM quantum computers, calculating the Rényi entanglement entropy, the twist order parameter, and the Berry phase. The latter two quantities can be deduced from a slow-twist operator defined in the Lieb-Schultz-Mattis theorem. The Rényi entropy is obtained using a recently developed randomized measurement scheme. The twist order parameter and the Berry phase are measured without the need for additional gates or ancilla qubits. We consider quench protocols in which a trivial initial state evolves dynamically in time under the topological SSH Hamiltonian in the fully dimerized limit (the flat-band limit). During these quenches, there are persistent and periodic oscillations in the time evolution of both entanglement entropy and twist order parameter. Through the implementation of error mitigation techniques using a global depolarizing ansatz and postselection, our simulations on the IBM devices yield results that closely match exact solutions.